Pregnant-puerperal care in Network: the experience of nurses, doctors and administrators - Renata Andrade Teixeira; Rosângela Aparecida Pimenta Ferrari; Sebastião Caldeira; Mauren Teresa Grubisich Mendes Tacla; Adriana Valongo Zani
ABSTRACT Objective: Understand the experience of nurses, doctors and administrators of pregnancy-puerperal cycle care to women in the Rede Mãe Paranaense (Freely translated as Paranaense Mother Network). Method: Qualitative research according to social phenomena with 44 professionals from 10 municipalities of the Regional of Health, in Paraná State, Brazil. The testimonies were recorded until converge and were analyzed following the steps established from the background. Results: It was understood a content of meaning experienced among different professional classes. The "motives why" in which the Network was a reasoned proposal to improve the mother care quality, although there is disarticulation in the planning and application. The expectation for "motives for" proved fragility and challenges to reach the goals and aims of the Network in the Primary Health Care practice. Final considerations: The Network reorganization was carried out, but there are gaps in the reference and counter-reference system, especially for the pregnancy and high risky childbirth and puerperal cycle.